Constitutive activation of distinct NF‐κB signals in EBV‐associated nasopharyngeal carcinoma. Issue 3 (3rd September 2013) - Chung, Grace Tin‐Yun; Lou, Wilson Pak‐Kin; Chow, Chit; To, Ka‐Fai; Choy, Kwong‐Wai; Leung, Alice Wan‐Chi; Tong, Carol Yuen‐Kwan; Yuen, Jessie Wai‐Fong; Ko, Chun‐Wai; Yip, Timothy Tak‐Chun; Busson, Pierre; Lo, Kwok‐Wai
Abstract As a distinct type of head and neck cancer, non‐keratinizing nasopharyngeal carcinoma (NPC) is closely associated with EBV infection and massive lymphoid infiltration. The unique histological features suggest that local inflammation plays an important role in NPC tumourigenesis. We comprehensively characterized NF‐κB signalling, a key inflammatory pathway which might contribute to the tumourigenesis of this EBV‐associated cancer. By EMSA, western blotting, and immunohistochemical staining, constitutive activation of distinct NF‐κB complexes, either p50/p50/Bcl3 or p50/RelB, was found in almost all EBV‐positive NPC tumours. siRNA or chemical inhibition of NF‐κB signalling significantly inhibited the growth of EBV‐positive NPC cells C666‐1. Gene expression profiling identified a number of NF‐κB target genes involved in cell proliferation, apoptosis, immune response, and transcription. We further confirmed that p50 signals modulate the expression of multiple oncogenes (MYB, BCL2), chemokines, and chemokine receptors (CXCL9, CXCL10, CX3CL1, and CCL20). The findings support a crucial role of these constitutively activated NF‐κB signals in NPC tumourigenesis and local inflammation. In addition to expression of the viral oncoprotein LMP1, genetic alteration of several NF‐κB regulators (eg TRAF3, TRAF2, NFKBIA, A20) also contributes to the aberrant NF‐κB activation in EBV‐associated NPC. Except for LMP1‐expressing C15 cells, all NPC tumour lines harbour at least one of these genetic alterations. Importantly, missense mutations of TRAF3, TRAF2, and A20 were also detected in 3/33 (9.1%) primary tumours. Taken together with the reported LTBR amplification in 7.3% of primary NPCs, genetic alterations in NF‐κB pathways occurred in at least 16% of cases of this cancer. The findings indicate that distinct NF‐κB signals are constitutively activated in EBV‐positive NPC cells by either multiple genetic changes or EBV latent genes. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.